PERANCANGAN WEB COMIC SEBAGAI MEDIA PEMBELAJARAN PEMBENTUKAN HUJAN BAGI ANAK KELAS 3 SD Al-KAUTSAR - Adithya Pratama (Dimensi : Jurnal Ilmiah Komunikasi dan Seni Desain Grafis, 2022)
Research has been carried out to design a comic as a learning medium on rain formation material. The purpose of this design is to produce a comic that can be used as a learning medium to help students understand the rain formation material in depth. The design procedure includes analysis of teacher needs, material collection, product design, validation of material experts and design experts, revisions, field trials, and final products adapted from the development process initiated by borg and gall. The results showed that the designed product was very feasible to use because it was attractive and easy to use and very useful with a percentage of assessment of feasibility as much as 86% in field trials.